Design of Integrated Rectangular SIW Filter and Microstrip Patch Antenna - Zakaria, Z; Sam , W. Y; Abd Aziz, M. Z. A.; Awang Md Isa, Azmi; Mohd Johar, Fauzi (2012)
This paper presents a new class of integrated rectangular Substrate Integrated Waveguide (SIW) filter and microstrip patch antenna for RF/microwave front-end subsystems. To validate this concept, the integrated microwave filter and antenna based upon a cascaded approach at center frequency of 2 GHz is demonstrated and verified through simulation and measurement. Experimental results show good agreement with simulated results. This study also proposes a new technique to integrate the rectangular SIW filter and the microstrip patch antenna based upon the multilayered approach. The simulation is implemented using FR-4 on a 1.6 mm dielectric substrate thick with dielectric constant = 4.6. The simulation performance shows promising results that could be further proved during the experimental works. This study is useful for any microwave system design where the reduction of overall physical volume and weight as well as cost is very important.